Carotid body denervation improves autonomic and cardiac function and attenuates disordered breathing in congestive heart failure. (15th January 2014) - Marcus, Noah J.; Del, Rodrigo; Schultz, Evan P.; Xia, Xiao‐Hong; Schultz, Harold D.
Key points A strong correlation between disordered breathing patterns, elevated sympathetic nerve activity and enhanced chemoreflex sensitivity exists in patients with heart failure. Evidence indicates that disordered breathing patterns and increased sympathetic nerve activity increases arrhythmia incidence in patients with heart failure. Enhanced coupling between sympathetic and respiratory neural drive underlies elevated sympathetic nerve activity in an animal model of sleep apnoea. We investigated the impact of carotid body chemoreceptor denervation on sympathetic nerve activity, disordered breathing and sympatho‐respiratory coupling in an animal model of heart failure. Renal sympathetic nerve activity, apnoea/hypopnoea incidence, variability measures of tidal volume and respiratory rate and arrhythmia incidence were quantified during resting breathing in heart failure animals with and without carotid body ablation. Our results indicate that carotid body chemoreceptor denervation reduces sympathetic nerve activity, disordered breathing patterns, arrhythmia incidence and sympatho‐respiratory coupling in experimental heart failure. These findings suggest that device‐oriented ablation of carotid body chemoreceptors is a viable treatment option for reduction of sympathetic nerve activity, disordered breathing patterns and arrhythmia incidence in heart failure.